2014
DOI: 10.1108/bfj-05-2012-0114
|View full text |Cite
|
Sign up to set email alerts
|

Young adults and wine consumption a qualitative application of the theory of planned behavior

Abstract: Purpose – The aim of this study is to identify perceptions, attitudes and behavior of young adults concerning wine consumption, using the “theory of planned behavior” as a theoretical framework. Design/methodology/approach – The aim of this study is to identify perceptions, attitudes and behavior of young adults concerning wine consumption, using the “theory of planned behavior” as a theoretical framework. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 30 publications
0
20
0
5
Order By: Relevance
“…), but we can even find fewer studies that focused their population study on the youth segment [9]. Thus, as Silva, Figueiredo, Hogg, and Sottomayor [10] suggested, research has focused primarily on quantitative studies on trends in wine consumption in adults, and when they have focused on the youth group, they have only focused on issues related to consumer abuse [11][12][13][14]. Nevertheless, some knowledge of the elements that motivate the non-abusive consumption of wine among young people will help wine producers have a better idea of how future consumers will react, as well as to better understand their expectations [15].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…), but we can even find fewer studies that focused their population study on the youth segment [9]. Thus, as Silva, Figueiredo, Hogg, and Sottomayor [10] suggested, research has focused primarily on quantitative studies on trends in wine consumption in adults, and when they have focused on the youth group, they have only focused on issues related to consumer abuse [11][12][13][14]. Nevertheless, some knowledge of the elements that motivate the non-abusive consumption of wine among young people will help wine producers have a better idea of how future consumers will react, as well as to better understand their expectations [15].…”
Section: Introductionmentioning
confidence: 98%
“…In this sense, research on the preferences of young people for the attributes of wine has concluded that characteristics such as price, taste and brand value are reasons related to their choice [16][17][18]. In the case of young people, the price of wine is one of the main reasons that can lead to the choice of cheaper alcoholic beverages [19][20][21], and the taste of wine is frequently indicated as the main reason for aversion among young non-consumers [10]. Therefore, as Capitello, Agnoli, and Begalli [22] pointed out, when it comes to reaching young consumers, marketing approaches should be specially adapted to them, promoting communication for educational purposes, acknowledging intrinsic and sensorial signals of wine, such as aroma and flavor, among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their impacts are supposed to be in line, which is the possessions can be demonstrated by means of preservative prototypes. Silva, Figueiredo, Hogg and Sottomayor (2014) said that intention heads straight away to behavior, and is resolute by the collaboration of three dissimilar and significant experiences: attitudes, subjective norms and perceived behavior controls. Attitude toward the behavior is an individual's global valuation of the behavior.…”
Section: Attitude Link To Behaviormentioning
confidence: 99%
“…Attitude toward the behavior is characterized as "a man's general sentiment idealness or un-favorableness for that behavior". Silva, Figueiredo, Hogg and Sottomayor (2014) said that intention heads straight away to behavior, and attitude toward the behavior is an individual's global valuation of the behavior. Healy, Joram, Matvienko, Woolf and Knesting (2015) investigated the Impact of an intuitive eating education program on high school students eating attitudes and suggested that IE instruction persuade the attitude on eating healthy.…”
Section: Attitude Link To Behaviormentioning
confidence: 99%